Normative Character of E-RUPS Implementation Share Open Company - Ikhsan Lubis (DE LEGA LATA: JURNAL ILMU HUKUM, 2022)
This study aimed to analyze the normative character of the application of the provisions of POJK No. 15/POJK.04/2020 and POJK No. 16/POJK.04/2020 holding the General Meeting of Shareholders electronically (abbreviated: e-GMS) for Public Companies, and the type of research used was normative legal research. This research used several approaches, such as: statute approach (legal approach) and conceptual approach (concept approach), and the results of the research showed that the implementation of the e-GMS is regulated in POJK No. 15/POJK.04/2020 and POJK No. 16/POJK.04/2020 can be used as a legal basis that can provide legal certainty in the context of organizing e-GMS for Public Companies through the implementation of procedures and procedures for determining the location of the GMS, fulfilling the attendance quorum, decision-making quorum and the form of minutes of GMS decisions by using teleconferencing media, video conferences, or other electronic media means